Comparison of Health Care Needs of Child Family Members of Adults with Alcohol or Drug Dependence Versus Adults with Asthma or Diabetes - Ray, G. Thomas (2014)
OBJECTIVE: To compare the health problems, preventive care utilization, and medical costs of child family members (CFMs) of adults diagnosed with alcohol or drug dependence (AODD) to CFMs of adults diagnosed with diabetes or asthma. METHODS: Child family members of adults diagnosed with AODD between 2002 and 2005 and CFMs of matched adults diagnosed with diabetes or asthma were followed up to 7 years after diagnosis of the index adult. Logistic regression was used to determine whether the CFMs of AODD adults were more likely to be diagnosed with medical conditions, or get preventive care, than the CFMs of adults with asthma or diabetes. Children’s health services use was compared using multivariate models. RESULTS: In Year 5 after index date, CFMs of adults with AODD were more likely to be diagnosed with depression and AODD than CFMs of adults with asthma or diabetes and were less likely to be diagnosed with asthma, otitis media, and pneumonia than CFMs of adults with asthma. CFMs of AODD adults were less likely than CFMs of adult asthmatic patients to have annual well-child visits. CFMs of AODD adults had similar mean annual total health care costs to CFMs of adults with asthma but higher total costs ($159/yr higher, confidence interval, $56–$253) than CFMs of adult diabetic patients. CFMs of adults with AODD had higher emergency department, higher outpatient alcohol and drug program, higher outpatient psychiatry, and lower primary care costs than CFMs of either adult asthmatic patients or diabetic patients. CONCLUSION: Children in families with an alcohol- or drug-dependent adult have unique patterns of health conditions, and differences in the types of health services used, compared to children in families with an adult asthmatic or diabetic family member. However, overall cost and utilization for health care services is similar or only somewhat higher. This is the first study of its kind, and the results have implications for the reduction of parental alcohol or drug dependence stigma by health care providers, clearly an important issue in this era of health reform.